Strategies for Peer Teaching to Promote Collaborative Skills in Primary and Junior High School Students - Ge, Mengjun (International Journal of Humanities and Education Development (IJHED), 2023)
"Practice, active exploration, and cooperative exchange should be an important way for students to learn knowledge", which is the latest requirement of the New Curriculum Standard, and is an indispensable factor for students to adapt to society in the future and gain a foothold in society. Through peer teaching, students will be guided to work together gradually according to the physical and mental characteristics of primary and secondary school students. They will exchange various ways of thinking and exploring in the process of peer education, and through interaction, cultivate their thinking ability, raise their awareness of collaboration, and enhance their ability to collaborate. Students will learn how to work together and take the initiative to work together to meet the demands of our era and our society.